KOMUNIKASI INTERPERSONAL ORANG TUA DENGAN ANAK DALAM MENCEGAH KENAKALAN REMAJA DI NAGARI TARUANG-TARUANG - Andi Saputra (Jurnal Komunikasi, 2025)
This research is motivated by the large number of teenagers engaging in deviant behavior, for example often participating in brawls, lack of manners in speaking to their elders, many people smoking, skipping school, drinking and playing online games, so they forget the time to carry out their responsibilities as children for school. and learn properly. This research aims to determine interpersonal communication between parents and children in preventing juvenile delinquency in Nagari Taruang-Taruang as well as the factors that hinder interpersonal communication between parents and children in preventing juvenile delinquency in Nagari Taruang-Taruang. The research method used is the Qualitative Method. The main source of this research is communication between parents and children in preventing juvenile delinquency in Nagari Taruang-Taruang. Data collection techniques are observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions or verification. The results of this research are that interpersonal communication between parents and children to prevent juvenile delinquency in Nagari Taruang-Taruang is that first, parents always give advice to their children, provide good direction to their children, and always provide religious messages to educate their children as well as include moral education and morals so that the child avoids juvenile delinquency